Case report papers guidelines: Recommendations for the reporting of case studies or action research in Business Management - Juan A. Marin-Garcia; Jose P. Garcia-Sabater; Julien Maheut (WPOM : Working Papers on Operations Management)
Objective: To provide a working guide which facilitates the accuracy, transparency, and usefulness for academics and practitioners of case report papers as an article type which are fit for publishing in impact journals. In this way, we aim to increase the use and dissemination of recommendations in aid of the writing and publication of case study and action research.